2017
DOI: 10.3892/etm.2017.4827
|View full text |Cite
|
Sign up to set email alerts
|

Doxazosin attenuates renal matrix remodeling mediated by anti-α1-adrenergic receptor antibody in a rat model of diabetes mellitus

Abstract: Diabetic nephropathy is a major complication of diabetes mellitus (DM). Recent studies suggest that immunological mechanisms have a key role in the pathogenesis of DM, therefore these mechanisms may be important targets for diabetes therapy. The present study evaluated the effects of anti-α1-adrenergic receptor antibody (α1-R Ab) mediation and doxazosin treatment in a rat model of DM. It was observed that levels of 24-h urinary protein, serum creatinine and transforming growth factor-β1 in DM were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…An animal experiment by a Chinese research group has shown that the holes in the kidney in diabetic rats are first formed by agAAB against the α1-AR [21]. 100 | a r c h i v e u r o m e d i c a | 2 0 1 9 | v o l .…”
Section: E T H O D S / M a T E R I A Lmentioning
confidence: 99%
“…An animal experiment by a Chinese research group has shown that the holes in the kidney in diabetic rats are first formed by agAAB against the α1-AR [21]. 100 | a r c h i v e u r o m e d i c a | 2 0 1 9 | v o l .…”
Section: E T H O D S / M a T E R I A Lmentioning
confidence: 99%
“…Alpha 1 adrenoceptor autoantibodies have been objectified in some patients with diabetic nephropathy, with deleterious effects on kidney and arterial pressure [33-34]. These autoantibodies seem to be of stimulatory nature, as their effects are contracted by the alpha 1 adrenoceptor antagonists [33-34]. This led to the suggestion that HA1A may be harmful to the kidney.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, the patients may suffer from hypoglycemia, insulin resistance, weight gain, gastrointestinal adverse reactions, and liver and kidney damage [2]. Thus, developing a rational drug therapy is valuable to patients with type 2 diabetes mellitus [3]. This study aims to explore the value of invigorating qi, nourishing yin, and promoting blood circulation in ensuring clinical treatment efficacy and favorable prognosis for patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%